A layer-by-layer deposition strategy of fabricating NiO@rGO composites for advanced electrochemical capacitors. (10th January 2015) - Zhang, Haiming; Guo, Di; Zhu, Jian; Li, Qiuhong; Chen, Libao; Wang, Taihong
Highlights: Layered NiO@rGO composites supported on nickel foam was realized by an one step binder-free ESD approach. The diameter of the NiO nanograins anchored on rGO was ∼2.9nm. Abstract: Although graphene oxide (GO) can be well dispersed in aqueous solution, direct reduction of GO in solution usually results in irreversibly precipitated agglomerates due to strong π-π interactions. Such a problem could be avoided by preparing layered graphene-based materials using an electrostatic spray deposition (ESD) technology. A composite film consisting of NiO nanograins@reduced graphene oxide nanosheets (NiO@rGO) with layered structure was realized by a facile one step binder-free ESD approach. It was deposited directly onto the nickel foam and showed excellent electrochemical capacitor properties, about 881 F g −1 at a current density of 0.5 A g −1 and 667 F g −1 at 50 A g −1 with an excellent cycling ability. Furthermore, this technique opens a new access to the preparation of layered graphene based composites with novel structures and properties.